1994
DOI: 10.1093/jac/34.4.507
|View full text |Cite
|
Sign up to set email alerts
|

Farm animals as a putative reservoir for vancomycin-resistant enterococcal infection in man

Abstract: Using a highly selective enrichment broth, 62 isolates of vancomycin-resistant Enterococcus faecium were obtained from non-human sources; 35 isolates from raw sewage, 22 from farm animals and 5 from uncooked chickens. All strains possessed the Van A gene, conferring high-level resistance to vancomycin (MIC > or = 256 mg/L). Ribotyping of 42 of these isolates resulted in 14 distinguishable patterns. Two ribotyping patterns were found among isolates from animals and sewage and those from clinical sources. A bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
238
2
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(253 citation statements)
references
References 0 publications
7
238
2
3
Order By: Relevance
“…Earlier studies revealed that use of fluoroquinolones in poultry was not appropriate due to the cross-resistance with fluoroquinolones used to treat human enteric infections. High resistance to chlortetracycline and oxytetracycline is of major concern because of the use of the same antibiotics in human medicine and poultry or in other food animals and the emergence of drug-resistant human pathogen [15] [16]. Antibiotic resistance of fecal E. coli was greater in broilers and turkeys that received antibiotics relatively frequently compared to layers, which had little exposure to antibiotics [14].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies revealed that use of fluoroquinolones in poultry was not appropriate due to the cross-resistance with fluoroquinolones used to treat human enteric infections. High resistance to chlortetracycline and oxytetracycline is of major concern because of the use of the same antibiotics in human medicine and poultry or in other food animals and the emergence of drug-resistant human pathogen [15] [16]. Antibiotic resistance of fecal E. coli was greater in broilers and turkeys that received antibiotics relatively frequently compared to layers, which had little exposure to antibiotics [14].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that as much as 80% of total antibiotic production in the United States is used in agriculture, with a substantial portion of this used for the nontherapeutic purpose of growth promotion (4,5). AR bacteria have been found in farm animals where antibiotics are heavily used (6)(7)(8), in associated food products (9,10), in environments contaminated by animal waste (11,12), and in farm workers (13)(14)(15). Drugs that are used therapeutically in animals also may generate a reservoir of AR bacteria (16,17).…”
mentioning
confidence: 99%
“…Recent studies from several countries in Europe have shown a strong association between the use of avoparcin as a growth promoter for animals and the occurrence of VRE in animals and food (Bates et al, 1994;Aarestrup, 1995;Klare et al, 1995;Bager et al, 1997). The detection of VRE in livestock and fresh meat suggests that humans are exposed to VRE either by direct contact with animals or from consumption of meat.…”
Section: Avoparcin/vancomycinmentioning
confidence: 99%